Rapid scale-up of hospital-at-home services during wartime: lessons learned from the Sheba Medical Center experience - Anat Ekka Zohar; Boris Fizdel; Liat Aroshass; Liron Vaserman; Galia Barkai; Shani Edelman; Rachel Sarafraz; Eyal Leshem; Matan Peri; Asaf Biber; Yael Frenkel Nir; Gad Segal (Frontiers in Medicine, 2026)
Background Sheba BEYOND, the telemedicine-governed hospital within the Sheba medical center includes a unique telemedicine-based service for internal-medicine patients suffering from acute illness since 2020, serving as a viable alternative to in-hospital stay. During March 2026, amid an Israeli war on two fronts, Iran and Lebanon, the urgent need to transfer over 1,900 (in-hospital) patients to underground facilities under continuous missile attacks necessitated immediate, massive fortification of our HaH services across multiple clinical disciplines. Methods Sheba BEYOND qualified its HaH services for home hospitalization of dozens of patients from several clinical disciplines. Both its headquarters, in-house and external nursing services and physicians had to rapidly scale up. We did a descriptive analysis and comparison of HaH activities between wartime (March 2026) and the previous month (February 2026). Results During March 2026, mean daily HaH admissions increased almost three-fold, from 2.11/day to 6.06/day, corresponding to a rate ratio of 2.88 (95% CI 2.15–3.86; p < 0.001). Patients admitted during wartime were younger than those admitted pre-war (mean age 63.1 ± 20.6 vs. 71.5 ± 16.4 years, p = 0.002), and the clinical scope expanded from internal medicine to include surgical, pediatric, cardiology, gynaecology, and oncology patients. Operational capacity expanded from 12 to 40 HaH beds, the nursing workforce increased through recruitment of 30 additional nurses, and geographic coverage expanded from a 30-km radius to nationwide service using internal and external nursing providers. Short-term clinical indicators did not show statistically significant worsening: transfers back to hospital were 6.8% vs. 2.1% ( p = 0.095), repeat hospital admission within 14 days was 8.5% in both groups, median HaH length of stay was 3 days in both periods (IQR 2–5 in both; p = 0.295), and no patient died during active HaH care. Because of important differences in age and case mix, these unadjusted clinical comparisons should be interpreted cautiously. Conclusion This wartime experience demonstrates that a telemedicine-led HaH service can be rapidly scaled in volume, geographic reach, and clinical scope during a hospital capacity crisis. The available data support the feasibility of rapid operational expansion and provide reassuring, but unadjusted, short-term safety indicators rather than definitive evidence of clinical equivalence.